Cardiac EGM Automatic Screening of egms transmitted by Implantable Electronic Devices - Narimane Gassa; Benjamin Sacristan; Nejib Zemzemi; Maxime Laborde; Juan Garrido Oliver; Clara Matencio Perabla; Guillermo Jimenez-Perez; Oscar Camara; Sylvain Ploux; Marc Strik; Pierre Bordachar; Remi Dubois (Zenodo, 2021)
This is an abstrat submitted and accepted in the CinC conference 2021